Răspuns :
a)
-13 - x + 5 = -143
-x = -143 - 5 + 13
-x = -148 + 13
-x = -135
x = - 135 / -1 ⇒ x = 135
b)
x · (-17) = -34
-17x = -34
x = -34 / -17 ⇒ x = 2
-13 - x + 5 = -143
-x = -143 - 5 + 13
-x = -148 + 13
-x = -135
x = - 135 / -1 ⇒ x = 135
b)
x · (-17) = -34
-17x = -34
x = -34 / -17 ⇒ x = 2
[tex]a) - 13 - x + 5 = - 143[/tex]
[tex] - x = - 143 + 13 - 5[/tex]
[tex] - x = - 130 - 5[/tex]
[tex] - x = - 135 \: | \times ( - 1)[/tex]
[tex]x = 135[/tex]
[tex]b)x \times ( - 17) = - 34 \: | \div ( - 17)[/tex]
[tex]x = 2[/tex]
[tex] - x = - 143 + 13 - 5[/tex]
[tex] - x = - 130 - 5[/tex]
[tex] - x = - 135 \: | \times ( - 1)[/tex]
[tex]x = 135[/tex]
[tex]b)x \times ( - 17) = - 34 \: | \div ( - 17)[/tex]
[tex]x = 2[/tex]